Identifying the level of community involvement in the community activities at Kg. Kuala Telang, Kuala Lipis, Pahang - Yaman, Maheran; Baharuddin, Zainul Mukrim; Md Jani, Haza Hanurhaza (Malaysian Institute Of Planners, 2018)
A community is a particular group of people that are bound by a similar cultural practice and activities. The continuation of the practising the local culture developed an identity for the community. Through time, the identity is strengthened by the level of community involvement in response to their participation in preserving the culture. The lack of community involvement would result to decreasing number of cultural practices. Eventually, the process contributed to a negative impact on the local identity. This paper addresses the importance of a community involvement concerning safeguarding the local culture and practices. Two objectives are outlined in achieving the aim. Firstly, to identify the list of the community activities. Secondly, to determine the level of community involvement at Kg. Kuala Telang, Kuala Lipis. A quantitative method of analysis is adopted in the paper to achieve the objectives. The survey questionnaire is distributed to 58 respondents, and the result is analysed using descriptive statistics and Spearman correlation tests. The findings from the data collection are arranged into four categories, and the result is discussed accordingly as to answer the aim and objectives of the paper. As a final remark, the paper highlights the importance of community involvement and the methods to ensure the level of participation in response to community activities in the village.